PENGGUNAAN ALAT PERAGA MATEMATIKA PADA MATERI PELUANG - Ari - Indriani (Universitas Pekalongan, 2019)
Problems that want to be investigated in this research is any props which can be used for opportunity material specially look for opportunity an event? While this study aims to introduce the type of mathematical props to teach the material opportunities, especially to look for opportunities an incident. This research includes qualitative descriptive research, with research subject props generated by students of Mathematics Education Study Program. Data collection methods used were interview method and documentation method. The conclusions in this study are mathematical props which are made to look for chance of an occurrence such as: chance round, stork full color, mathematical rainbow ball, fugitive math / color wheel, probability glass, rotating board, permutation hanger, almanac binary, and hanging. The props are used and simplify the students' concepts in studying the probability of an event, in which the probability formula of an event is P(A)=n(A)/n(S).